MYSTICAL EXPERIENCE IN SUFISM THE STUDY OF UNIQUENESS OF SUFISM IN RELATION TO MYSTICISM - Arifka, Angga (Universitas Islam Indonesia, 2025)
This article investigates Sufism and its closeness with the so-called mysticism. Indeed, mysticism is chiefly characterized by mystical experience, referring to, broadly speaking, that of union with the ultimate reality. On this basis, Sufism also evinces mystical experience from which the Sufis elaborate some terminological concepts such as fanā’, wahdat al-wujūd, ittihād, etc. As a qualitative study with a type of library research, this article employs content analysis to provide an in-depth interpretation of the texts analyzed, especially literature relevant to the field of study. The results of the analysis demonstrate twofold. On the one hand, Sufism is arguably Islamic mysticism due to its emphasis on mystical experience about God. On the other hand, Sufism has its own uniqueness since it also pays much attention to moral development and human behavior. In addition, Sufism has great contribution and significance to Islamic civilization in particular and modernity in general, ranging from Islamic psychology, metaphysics, art and literary world to human peace and spiritual crisis.